Improved Listeria monocytogenes selective agar. - Lee, W H (1986)
By increasing the LiCl concentration to 5 g/liter and adding 20 mg of moxalactam per liter to modified McBride agar base, it was possible to inhibit the growth of many bacteria which interfered with the recovery of Listeria monocytogenes from beef.